Enhanced Warming and Intensification of the Kuroshio Extension, 1999–2013 - You-Lin Wang; Chau-Ron Wu (Remote Sensing, 2019)
The Pacific climate regime has anomalous warm and cool periods every decade associated with atmospheric circulation changes, which are known to have modulated the tropical and subtropical Pacific during the recent Pacific hiatus regime (1999–2013). However, the influence of the hiatus regime on the Kuroshio Extension (KE) remains unclear. Here, we show that the KE jet underwent enhanced warming (increased 1–1.5 °C), intensification (8–19%) and northward migration (0.5–1°). The KE jet became more perturbed in the upstream region (increased by 70%, west of 146°E) but became stable downstream (perturbation decreased 5–11%, east of 146°E). A poleward shift of the mid-latitude jet stream and weakened Aleutian Low (AL) contributed to the northward migration and intensification of the KE jet, respectively. The weakened AL was associated with negative wind stress curl (WSC) in the eastern Pacific, and this WSC generated an underlying positive sea surface height anomaly that propagated westward, intensifying the KE jet when it reached the KE region. Since the recent Pacific hiatus regime ended after 2013, these changes of the KE jet may reverse during the ongoing warming regime.